2008
DOI: 10.1021/ja8037068
|View full text |Cite
|
Sign up to set email alerts
|

Role of Host Layer Flexibility in DNA Guest Intercalation Revealed by Computer Simulation of Layered Nanomaterials

Abstract: Layered double hydroxides (LDHs) have been shown to form staged intermediate structures in experimental studies of intercalation. However, the mechanism by which staged structures are produced remains undetermined. Using molecular dynamics simulations, we show that LDHs are flexible enough to deform around bulky intercalants such as deoxyribonucleic acid (DNA). The flexibility of layered materials has previously been shown to affect the pathway by which staging occurs. We explore three possible intermediate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 67 publications
2
57
0
2
Order By: Relevance
“…Such strategy for construction of PCL material is based on the fact that the LDH nanosheets are flexible enough to deform over interlayer bulky guests, and slipping of LDH layer can occur on increasing the external pressure, which can further influence the host-guest interactions [21]. In addition, the long-chain BTZB anion has four rotatable aromatic amine units, and thus its molecular conformation and intermolecular interactions can be tuned more easily by external perturbations than the rigid molecules.…”
Section: Ldh-based Physicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Such strategy for construction of PCL material is based on the fact that the LDH nanosheets are flexible enough to deform over interlayer bulky guests, and slipping of LDH layer can occur on increasing the external pressure, which can further influence the host-guest interactions [21]. In addition, the long-chain BTZB anion has four rotatable aromatic amine units, and thus its molecular conformation and intermolecular interactions can be tuned more easily by external perturbations than the rigid molecules.…”
Section: Ldh-based Physicalmentioning
confidence: 99%
“…A previous review on LDH-based fluorescent materials has mainly summarized the preparation method and tunable photoluminescent properties [19]. Recently, the host-guest stimuli-responsive luminescent materials have also been studied successively, since the orientation mode of the interlayer chromophores and hostguest interaction can be changed upon external stimuli [20,21]. In addition, new physical/chemical phenomena have also been obtained based on the theoretical calculations for these hybrid nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[153,154] So, a 1 µm GRcarb would be about 100 nm thick and comprise ~130 double layers overall. [154,155,156,157,158] The height of the hydroxyl interlayer galleries is ~0.30 nm, allowing them perhaps to act as anion and proton channels. And the Fe 2+ -Fe 3+ distance of ~0.33 nm along the iron layers would allow electron hopping by quantum tunneling, though a small proportion of electrons could also jump across the layers.…”
Section: Green Rust -The First Organizing Nanoengine Of Life?mentioning
confidence: 99%
“…3C) [54,55]. As a result of molecular dynamic modeling, it was found that the LDH layers are flexible enough to deform around bulky DNA molecules.…”
Section: Structural Features and Chemical Bonding Naturementioning
confidence: 99%